Jatropha (Jatropha curcas) meal is an alternative protein source in poultry nutrition. Issue 4 (17th October 2017) - SAEED, M.; ARAIN, M.A.; ARIF, M.; LAGAWANY, M.; ABD EL-HACK, M.E.; KAKAR, M.U.; MANZOOR, R.; ERDENEE, S.; CHAO, S.
Abstract : The application of novel feedstuffs in poultry diets, especially in developing countries, has received attention in recent years. Jatropha ( Jatropha curcas ) is a non-edible oil seed, and its meal is a rich in protein. Jatropha meal (JM) has been characterised as a potentially useful animal feedstuff due to its high content of crude protein level (35-50%), essential amino acid and mineral content. However, jatropha kernel contains high amounts of phytate, ranging from 7 to 10%, which would require phytase supplementation for it to be used in feeds. Jatropha contains toxic compounds and anti-nutritional factors, including lectin, tannin, saponin, phorbol esters and trypsin inhibitors, which require different treatments (physical, chemical or biological) to make it suitable for poultry diets. As a result of the presence of detrimental compounds, only low levels of jatropha in feed are recommended from animal trials. It may be used to partially substitute soybean meal, but not maize. It has been suggested in the literature that, after physical or chemical treatment of jatropha seed meal, it may have other benefits, including as an immunomodulant and antioxidant, as well as hypocholestermic, antihypertensive, hepatoprotectant, antiretroviral, anti-inflammatory, analgesic and antibacterial properties. It appears that heat and enzyme treated jatropha could be used in poultry diets without detrimental effects on productive and reproductive performance and may promote health status in poultry.